Experimental study on the performance of trays solar still with cracks and reflectors. (April 2021) - Essa, F.A.; Abdullah, A.S.; Omara, Z.M.; Kabeel, A.E.; Gamiel, Y.
Highlights: Effect of creating cracks with different numbers on the trays surface is tested. Impact of internal and external reflectors on trays distiller performance is studied. Maximum distillate improvement was 104% for trays still over conventional one. Maximum efficiency of trays still was 51% compared to 35% for conventional one. Abstract: In the current research, we introduced a new concept of free water dripping on the basin water using cracks in the suspended trays of the trays solar still to break the boundary layers and surface tension of the basin water inside the trays solar distiller. This new technique would lead to improve the productivity of the solar still and reduce the cost of production water. The previous publications concerned with breaking the surface tension of basin water such as using fan, blades, forced water dripping and air bubbles inside the water depended on using traditional sources of energy, which have a negative effect on the cost of the distilled water. As a result, the effect of creating cracks in the trays surface on the performance of trays solar still was investigated. Besides, the influence of different numbers of cracks such as 7, 10, and 14 cracks was studied. For further improvement of trays still performance, internal and external reflectors were employed onto the trays still and tested. The experimental results obtained that the number of 10 cracks provided greater productivity compared to that obtained when using either 7 or 14 cracks, where the productivity was enhanced by 12%, 9%, and 8% at 10, 7, and 14 cracks, respectively. At 7 cracks, the total distillates of the reference still and trays still with internal and external mirrors were 2450 and 5000 mL/m 2 ·day, respectively with an enhancement percentage of 104%. Furthermore, the highest efficiency was obtained for the trays still with internal and external mirrors at 7 cracks, where it was 51% compared to 34.5% for the traditional distiller. The estimated average costs of one liter of fresh water for CSS and TSS are 0.033 and 0.021 /L, respectively.